2016
DOI: 10.1016/j.combustflame.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl substitution on the auto-ignition of C16 alkanes

Abstract: The autoignition quality of diesel fuels, quantified by their Cetane Number or Derived Cetane Number (DCN), is a critical design property to consider when producing and upgrading synthetic paraffinic fuels. It is well known that autoignition characteristics of paraffinic fuels depend on their degree of methyl substitution. However, there remains a need to study the governing chemical functionalities contributing to such ignition characteristics, especially in the case of partially branched ones, which have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Simulated hydroxyl time-history profiles during the oxidation of stoichiometric mixtures of the three surrogates (PRF 60, TPRF 60, and MCS) are presented in Fig. 7 at 20 bar and 650 K. Previous studies by Merchant et al [46] and others [41,47,48] have shown that OH radical profiles provide insights into the chemical kinetics of ignition processes. The initial growth of OH radicals is similar between all the fuels, but at ~5 ms the OH radical growth for MCS slows compared to that of PRF and TPRF.…”
Section: Low-temperatures Chemical Kinetic Analysismentioning
confidence: 96%
“…Simulated hydroxyl time-history profiles during the oxidation of stoichiometric mixtures of the three surrogates (PRF 60, TPRF 60, and MCS) are presented in Fig. 7 at 20 bar and 650 K. Previous studies by Merchant et al [46] and others [41,47,48] have shown that OH radical profiles provide insights into the chemical kinetics of ignition processes. The initial growth of OH radicals is similar between all the fuels, but at ~5 ms the OH radical growth for MCS slows compared to that of PRF and TPRF.…”
Section: Low-temperatures Chemical Kinetic Analysismentioning
confidence: 96%
“…The surrogates for FACE F and G successfully reproduce the two-stage ignition response observed in the respective fuels, but the pressure trace comparison for FACE F shows a slight discrepancy. This is because both the FACE F and G surrogates contain slightly less paraffinic CH3 groups than the fuels, and these groups have been shown to have a greater impact on the evolution of ignition processes [49,100]. FACE I and J and their MFG surrogates do not exhibit two-stage ignition in the temperature ranges studied in the RCM.…”
Section: Iqt Ignition Delay Timesmentioning
confidence: 97%
“…CH2/CH3 ratio also governs the ignition delay of n-paraffin fuels in the boiling range of diesel fuels [48,49]. Though shown to be very constraining information, clearly the simple CH2/CH3 molecular structure metric of Won et al [47] is inadequate to differentiate the different combustion kinetic behaviors that are due to the isomeric arrangement of the fragments comprising such molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the autoignition chemistry is evolving as the temperature evolves, and the maximum temperatures reported in Table 3 may not be the most relevant parameters to fully understand autoignition chemistry in knocking engines. 61 For our study, one temperature and pressure were chosen for each of the RON and MON conditions, which enabled a common basis for comparing the underlying chemical kinetic phenomenon driving the reactivity of different fuels.…”
Section: Methodsmentioning
confidence: 99%